Flipped classrooms and their effect on Omani students’ vocabulary achievement and motivation towards learning English - Amal Mohammed Bati Al Qasmi; Thuwayba Al Barwani; Fawzia Al Seyabi (Intelektual Pustaka Media Utama, 2022)
This quasi-experimental study aimed to investigate the effect of the flipped classroom strategy (FCS) on Omani grade ten students’ vocabulary achievement and on their motivation towards learning English. This study also sought to explore the challenges that students face while learning via FCS. A total of 48 students participated in the study. There were 24 as an experimental group (taught via the FCS) and 24 as a control group (taught the same vocabulary using conventional teaching strategies). During the intervention, students in the experimental group practiced the core vocabulary using different materials (video clips, PDF files and group discussions via a WhatsApp group before carrying out face-to-face activities in the classroom). During the classroom time, the students engaged in activities with the practice materials individually, in pairs and in groups. The study used an achievement pre- and post-test. The study also used a motivation questionnaire (pre and post) to determine the students' motivation for English language learning for both groups. The findings indicated that the experimental group outperformed the control group in the vocabulary test and that they had high motivation towards learning English. In addition, the study also pointed out some of the challenges of learning via FCS such as connectivity issues, and lack of group cooperation. Considering these findings, practice implications and recommendations for further research are presented.